(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the positioning, concerns and difficulties of students and professors of higher education courses in the field of health in relation to distance learning during the coronavirus pandemic. Methods: Through WhatsApp Messenger, an anonymous questionnaire of google forms was sent to students and professors of higher education in health courses. The questions were about personal information, feelings about the coronavirus pandemic, distance learning and how quarantine could affect higher education courses. The level of anxiety/stress with the pandemic and the level of concern about the impact of the pandemic in higher education were compared between men and women with independent t test. Results: 704 students and 104 professors answered the questionnaire, with an average age of 23.09 years and 39.41 years, respectively. The students’ average level of anxiety/stress was 6.18. Women were significantly more anxious than men. Most students agreed to use distance learning. Both students and professors were concerned with the reduction in clinical and professional learning and with the way of teaching evaluation. The average level of concern related to the impact of the pandemic on higher education was 8.27 for students and 7.34 for professors. Conclusion: Students and professors were very concerned about the impact of the pandemic on learning and higher education, and felt that practical learning and professional and clinical training were hampered by the social isolation determined during the pandemic.